2010
DOI: 10.1002/cbic.201000392
|View full text |Cite
|
Sign up to set email alerts
|

Trap‐Closing Chemical Factors of the Venus Flytrap (Dionaea muscipulla Ellis)

Abstract: Be my guest! A macrocyclic hexamer, the structure of which is reminiscent of part of the bamboo‐plant stem (see picture), was directly prepared by the condensation of a glycoluril derivative and formaldehyde. The macrocycle bound halide anions with high affinity and selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The rapid closing of leaves (or trap) occurs when at least two sensor hairs respond to stimulus and chemicals are released, signalling specified leaves to close (Ueda et al . ). Debates about chemical signalling challenge our ideas about passivity, by suggesting that plants perceive, process and react to environmental information.…”
Section: The Lively Capacities Of Plantsmentioning
confidence: 97%
“…The rapid closing of leaves (or trap) occurs when at least two sensor hairs respond to stimulus and chemicals are released, signalling specified leaves to close (Ueda et al . ). Debates about chemical signalling challenge our ideas about passivity, by suggesting that plants perceive, process and react to environmental information.…”
Section: The Lively Capacities Of Plantsmentioning
confidence: 97%
“…Researchers have also begun to discover the biomolecular components underlying this electrical memory. Ueda and co-workers [47] demonstrated that there exists a threshold of accumulated bio-metabolite for stimulating trap closure. Using bioassays to separate Dionaea extracts, a bioactive polysaccharide was identified that is capable of triggering trap closure in absence of any external mechanical or electrical stimuli.…”
Section: E Electrophysiology Behind the Venus Flytrap's Fast Movementmentioning
confidence: 99%
“…The fact that electrical signals are important for sensing insect prey on the surface of a trap in some species of carnivorous plants has been known for centuries (Burdon‐Sanderson, ; Hodick & Sievers, ), but the role of jasmonates in botanical carnivory has been resolved only recently (Ueda et al ., ; Escalante‐Pérez et al ., ; Nakamura et al ., ; Libiaková et al ., ). Such similarity to plant defence is not surprising because it has previously been postulated that botanical carnivory probably evolved from plant defence mechanisms (Hatano & Hamada, ; Mithöfer, ; Rottloff et al ., ; Schulze et al ., ; Nishimura et al ., ; Pavlovič & Saganová, ; Bemm et al ., ; Krausko et al ., ).…”
Section: Introductionmentioning
confidence: 99%